The Effect of Block Coding (Scratch) Activities Integrated into the 5E Learning Model in Science Teaching on Students’ Computational Thinking Skills and Programming Self-Efficacy - Koray, Abdullah; Bilgin, Eda (Science Insights Education Frontiers, 2023)
This study was carried out to determine the effect of Scratch-based coding applications integrated into the 5E learning model used in science teaching on students’ computational thinking skills and self-efficacy towards block-based programming. In addition, students’ perceptions of the activity were measured after each Scratch activity, which was applied at different stages of the course and with different difficulty. The study employed the pretest-posttest control group less design, one of the quasi-experimental methods. The study sample consist of 22 6th grade students attending a public school in Turkey located in a district center in the Eastern Black Sea region. The study was carried out in a five-week period in the 2022-2023 academic years. Computational thinking scale and robotics attitude scale, self-efficacy perception scale related to block-based programming and activity perception scale were used as data collection tools. The data were analyzed using the dependent samples t-test. The findings suggest that computational thinking skills level of students and their self-efficacy perception related to block-based programming increased significantly with the Scratch-based activities integrated into 5E learning model applied in science subjects. In addition, students have positive attitudes towards these activities. Thus, it is recommended to apply Scratch-based coding applications in teaching science subjects.